Health Promoting Behaviors Among Persons at Risk of Stroke - พันธ์วิไล จตุพงษ์; สร้อยวงค์ ประทุม; สำราญญาติ มยุลี (Nursing Journal CMU, 2018)
Persons at risk of stroke will decrease their chances of experiencing a stroke, or reduce its severity, by performing health promoting behaviors. This descriptive study aimed to explore the health promoting behaviors among persons who are at risk of stroke in both caution and high risk groups, and who attended services at the outpatient department of Chiangmai Neurological Hospital from November 2015 to January 2016. The sample was purposively selected and consisted of 370 subjects at risk of stroke, of which 185 were drawn from the caution group and 185 from the high-risk group. Research instruments consisted of a demographic data record form, the Stroke Risk Scorecard developed by the National Stroke Association, and the Health Promoting Behaviors Among Persons at Risk of Stroke’s Questionnaire. Validity and reliability of the research instruments were approved prior to collecting data. Data were analyzed using descriptive statistics. The results revealed that: 1. The overall health promoting behaviors of the subjects in the caution group (68.11%) and high-risk group (60.00%) were at a high level. 2. For each subscale of health promoting behaviors in the caution and high-risk groups, over sixty-percent were at the high level, including spiritual growth, interpersonal relationship and stress management. 3. The health promoting behaviors subscales were reported by over half of the subjects in both groups as being at a moderate level, including health responsibility and nutrition. 4. The health promoting behaviors of physical activity subscale was at a high level in the caution group, while at a moderate level in the high-risk group. The results of this study show that the persons at risk of stroke demonstrate a high level of overall health promoting behaviors. It can imply that they perform an appropriate health promoting behavior. Further study should explore the factors related to their health promoting behaviors, especially health responsibility, physical activity, and nutrition subscales.